Discrete changes model of inter-core crosstalk of real homogeneous multi-core fibers - Cartaxo, A. V. T. (2017)
An analytical discrete changes model of the intercore crosstalk (ICXT) in real homogeneous weakly-coupled multicore fibers (cores with similar but different parameters) with bending and twisting perturbations is proposed for operation in the phase-matching region, where the bending radii are smaller than the critical bending radius. We show that this model is a generalization of the ICXT model proposed by other authors for perfectly homogeneous multi-core fibers (MCF). We compare simulation results of the coupled mode equation for a weakly-coupled step-index MCF with seven cores with theoretical predictions from the proposed model, and much faster and accurate mean ICXT power estimates are shown in the whole range of bending radii and difference of intrinsic effective refractive indexes corresponding to operation in the phase-matching region. We show that differences of mean ICXT power exceeding 4 dB can occur between the estimates provided by the model considering perfectly homogeneous MCF and the proposed model.